Language Diversity on Tourist Attraction Signs: A Case Study in Nakhon Pathom - Sirawich Tampanich; Virata Panjanon; Wattansak Fuengbangluang; Chayaphon Baicharoen; Hathaichanok Anghirun, (Journal of Communication in Scientific Inquiry (JCSI), 2024)
This linguistic landscape (LL) study is aimed to investigate the diversity of languages used on signs in the Nakhon Pathom province. This study was framed based on the reviewed empirical LL research studies previously conducted over the past decade. Nakhon Pathom was selected as the main research setting based on the convenient sampling method. Ten (10) most visited tourist attractions in Nakhon Pathom were chosen to be investigated. The samples of the study included 558 signs which were sorted into three categories based on recommendations by the Tourism Authority of Thailand (TAT): (1) history, religion, and museum, (2) nature and outdoor, and (3) food, shopping, and entertainment. Descriptive statistics, namely frequency and mean, were used to analyse the data. The findings revealed that the most commonly found signs were monolingual signs containing Thai or English (71%), bilingual signs containing Thai-English or English-Thai (28%), and multilingual signs containing Thai-English-Chinese, Thai-Chinese-English, Thai- Russian-Chinese, or Thai-English-Chinese-Japanese-Burmese (1%), respectively. According to the findings, Thai appeared to be the dominant language in majority of the examined signs, while multilingual signs were found the least, which expressed the multilingual needs for foreign tourists. Therefore, it is suggested that the local private and government sectors should provide more multilingual signs for a more effective communication and promote the tourism in Nakhon Pathom. For this reason, further research should put greater emphasis on the significance of language uses and symbols on public signs.